Rewriting the journey in contemporary Italian literature : figures of subjectivity in progress - Blum, Cinzia Sartini (Toronto Italian studies., 2008)
Sartini Blum demonstrate that women writers and migrant authors in contemporary Italy present journeys as events that are beyond heroic modern exploration and postmodern fragmentation.